Effects of Blended Learning Through LabRotation (BLLR) model on motivating high school students to learn chemistry subject - Almarzuqi, Ali Abdullah; Sulaiman, Tajularipin Bin; Mustakim, Siti Salina (Human Resources Management Academic Research Society (HRMARS), 2024)
Blended Learning Through Lab-Rotation (BLLR) model has emerged as a prominent educational approach, particularly in the context of motivating high school students to engage with the chemistry subject. This paper presents a comprehensive review of recent literature, to examine the effects of BLLR model on student motivation in chemistry education. The BLLR model integrates traditional classroom instruction with online learning activities and handson laboratory experiences, offering a dynamic and interactive learning environment tailored to diverse student needs. Motivation plays a critical role in shaping students' academic performance and long-term interest in chemistry. However, traditional teaching methods often fail to foster intrinsic motivation, leading to student disengagement. By synthesizing contemporary research findings, this paper explores how the BLLR model addresses motivational challenges through personalized learning experiences, real-world application of concepts, and collaborative inquiry-based activities. The synthesis of empirical evidence and theoretical frameworks underscores the transformative potential of BLLR model in enhancing student motivation and engagement in chemistry learning. Practical implications for educators and policymakers are discussed, along with recommendations for future research to further advance our understanding of blended learning's impact on student motivation in science education.